2021
DOI: 10.1038/s41586-021-04241-4
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution picture of kinship practices in an Early Neolithic tomb

Abstract: To explore kinship practices at chambered tombs in Early Neolithic Britain, we combined archaeological and genetic analyses of 35 individuals who lived about 5,700 years ago and were entombed at Hazleton North long cairn 1 . Twenty-seven are part of the first extended pedigree reconstructed from ancient DNA, a five-generation family whose many interrelationships provide statistical power to document kinship practices that were invisible without direct genetic data. Patrilineal descent was key in determining wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 47 publications
3
83
1
2
Order By: Relevance
“…Encouragingly, all data from the same individuals plots at the same position, consistent with the pattern observed in the first publication of Twist Ancient DNA data where Neolithic individuals from Hazleton North in southern Britain clustered tightly whether the data source was 1240k or Twist (39). That study also showed that Twist and 1240k data could be robustly co-analyzed to detect familial relatedness (39).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Encouragingly, all data from the same individuals plots at the same position, consistent with the pattern observed in the first publication of Twist Ancient DNA data where Neolithic individuals from Hazleton North in southern Britain clustered tightly whether the data source was 1240k or Twist (39). That study also showed that Twist and 1240k data could be robustly co-analyzed to detect familial relatedness (39).…”
Section: Resultssupporting
confidence: 85%
“…To explore how bias might affect our results, we began by projecting the data from the 15 libraries at the bottom of Table 1 onto a Principal Component Analysis of data from diverse present-day West Eurasian people living today (Figure 4). Encouragingly, all data from the same individuals plots at the same position, consistent with the pattern observed in the first publication of Twist Ancient DNA data where Neolithic individuals from Hazleton North in southern Britain clustered tightly whether the data source was 1240k or Twist (39). That study also showed that Twist and 1240k data could be robustly co-analyzed to detect familial relatedness (39).…”
Section: Figure 4: Principal Component Analysis Shows Similar Ancestr...supporting
confidence: 87%
See 1 more Smart Citation
“…A new study identifies close kin connected by patrilineal descent at the Cotswold–Severn chambered tomb at Hazleton North, Gloucestershire – importantly, this study combines 1240K genome-wide aDNA analyses with consideration of the placement of the dead in six distinct compartments which form two separate chambered areas. This integration of the genetic and contextual archaeological evidence allows the authors to identify that the locations within the tomb of 27 out of 35 sampled individuals are consistent with a virilocal patrilineal descent system in which maternal descent clusters were also significant (Fowler et al 2021). One male in the first generation reproduced with four women, and some of the descendants of two of these women were consistently placed in the south side of the tomb over several generations, suggesting that descent from a specific maternal ancestor was significant in deciding where to place the dead.…”
Section: Inferences About Kinship In Early Neolithic Britain and Irel...mentioning
confidence: 99%
“…To the best of our knowledge, no online pedigree programs offer analysis of relatedness, like coefficients of kinship and gene identity. Such coefficients play an important role in many fields, as exemplified by recent studies in quantitative genetics [ 5 ], forensic genetics [ 6 , 7 ] and ancient DNA [ 8 ]. Despite their widespread use, there is a serious lack of user-friendly software for computing relatedness coefficients, particularly for users without specialised bioinformatic skills.…”
Section: Introductionmentioning
confidence: 99%